"Like Holding an Umbrella Before It Rains": Acceptability of Future Rectal Microbicides Among Men Who Have Sex With Men in India—A Modified Technology Acceptance Model. (July 2017) - Chakrapani, Venkatesan; Newman, Peter A.; Shunmugam, Murali; Mengle, Shruta; Nelson, Ruban; Rubincam, Clara; Kumar, Pushpesh
Topical rectal microbicides (RMs) are a new prevention technology in development that aims to reduce the risk of HIV acquisition from anal sex. We examined RM acceptability among men who have sex with men (MSM) in India. We conducted a qualitative exploratory study guided by a modified Technology Acceptance Model, with 10 focus groups ( n = 61) of MSM and 10 key informant interviews. Data were explored using framework analysis. RM acceptability was influenced by technological contexts: perceived usefulness of RMs, perceived ease of use of RM and applicator, and habits around condom and lubricant use; individual and interpersonal contexts: perceived relevance and preferences for product formulation and dosing frequency; and MSM community/social contexts: perceived social approval, RM-related stigma, social support. Implementation of RMs for MSM in India may be supported by multi-level interventions that engage community-based organizations in destigmatizing and distributing RMs, ideally gel-based products that enable on-demand use before sex.